Acute effect of milk on serum urate concentrations: a randomised controlled crossover trial. Issue 9 (14th May 2010) - Dalbeth, Nicola; Wong, Sumwai; Gamble, Greg D; Horne, Anne; Mason, Barbara; Pool, Bregina; Fairbanks, Lynette; McQueen, Fiona M; Cornish, Jillian; Reid, Ian R; Palmano, Kate
Abstract : Objectives: Recent observational studies have highlighted the beneficial role of dairy ingestion in gout prevention. The aims of this study were to determine the acute effects of milk ingestion on serum urate concentrations and examine the mechanisms of these effects. Methods: This was a short-term randomised controlled crossover trial of milk in 16 healthy male volunteers. The following products were tested (each 80 g protein): soy control, early season skim milk, late season skim milk (containing high concentrations of orotic acid, a naturally occurring uricosuric agent) and ultrafiltrated MPC 85 skim milk. Each participant received a single dose of each product in random order. Serum and urine were obtained immediately before and then hourly over a 3 h period after ingestion of each study product. Results: Ingestion of the soy control led to an increase in serum urate concentrations by approximately 10%. In contrast, ingestion of all milks led to a decrease in serum urate concentrations by approximately 10% (p<0.0001). All products (including soy) rapidly increased the fractional excretion of uric acid (FEUA). Late season milk led to a greater increase in FEUA than MPC 85 (p=0.02) and early season milk (p=0.052). There were no differences over time in serum oxypurines or purine-containing nucleosides. However, all products increased the fractional excretion of xanthine. Conclusions: Intact milk has an acute urate-lowering effect. These data provide further rationale for long-term intervention studies to determine whether such dietary interventions have an adjunctive role in the management of individuals with hyperuricaemia and gout.